PERENCANAAN PROYEK PEMBANGUNAN JEMBATAN LUBUK JAMBI II KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Zeti Lestania; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Abstract The Lubuk Jambi II bridge construction project, KuantanMudikSubdistrict, KuantanSingingi Regency aims to improve the people's welfare with the state budget (APBN) of Rp 44,539,522,000. In the construction there are problems such as not achieving the completion of the project with a predetermined plan that development only lasts for one year, namely in early 2018 and operationalized in 2019, planning for environmental impact analysis is lacking in detail, land acquisition has not been completed to disrupt development implementation. This research aims to find out and analyze how the planning and inhibiting factors of the Lubuk Jambi II bridge construction project, KuantanMudik District, KuantanSingingi Regency. This research uses a qualitative method with a phenomenological approach. Data collection techniques through observation, interviews, and documentation. This method uses Ngurah planning theory with indicators of project objectives, job identification, budget planning, design, tender preparation and contract documents. From the results of the study, it was found that the development project planning was less thorough and not optimal because there were several inhibiting factors, namely unclear targets and direction, conflicts, unclear networking, budget. Keywords: development projects, Planning